Karyomorphology of skin diseases in human population - Sharma, Neha; Sharma, Sunita; Ganesh, N (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> The aim of the present study is to determine the incidence of chromosomal abnormalities in skin diseases. Patients were analyzed for chromosomal aberrations using peripheral lymphocyte culture. Cytogenetic analysis was carried out in 27 people affected by Vitiligo, Psoriasis, Parthenia. Lymphocytes culture was done and subjected to colcemid, hypotonic treatment, fixation and air drying.Â  GTG banded chromosomes were identified and counted for abnormalities. One way ANOVA was used to analyze the collected data. Tukey-Kramer Multiple Comparisons Test was used to determine differences between the means. Comparing the groups on the basis of type of chromosomal abnormalities, the differences between the means was found to be non significant (P>0.05) in all the comparisons. However, it was found to be significant for acrocentric association in Vitiligo subjects as compared to the controls. The means for premature centromeric divisions (Parthenia Vs Vitiligo) were also found to be significantly different.